2015
DOI: 10.1021/acs.energyfuels.5b00158
|View full text |Cite
|
Sign up to set email alerts
|

Combustion of n-Butanol, Gasoline, and n-Butanol/Gasoline Mixture Droplets

Abstract: Fuels derived from biofeedstocks are receiving attention for their potential as additives to conventional petroleum-based transportation fuels. Normal butanol, in particular, can enhance performance compared to ethanol because of its higher energy density. To better understand the combustion dynamics of n-butanol in the context of gasoline, experiments are reported here to examine the isolated droplet combustion characteristics of an 87 octane (ethanol-free) gasoline and a mixture of gasoline (0.9, v/v) and n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 65 publications
0
13
0
1
Order By: Relevance
“…Unlike ethanol, which can only be blended with hydrocarbon fuels up to certain limits due to its corrosivity and hydrophilicity, butanol is lipophilic and non-corrosive (New Zealand Ministry of Transport and SGS Industrial, Penrose 2009). Furthermore, it has a slightly higher energy density (36.0 MJ/L) than gasoline (34.2 MJ/L), and similar burn rate and octane number, allowing completely unmodified vehicles to run on both butanol alone and butanol/petrol fuel blends (Szulczyk, 2010;Xu and Avedisian, 2015). Butanol further allows higher ethanol concentrations to be used within blended fuels, as it solubilizes ethanol in the bulk petrol and prevents ethanol volatilization (Yanowitz et al, 2011).…”
Section: The Cost Of Carbon Capturementioning
confidence: 99%
“…Unlike ethanol, which can only be blended with hydrocarbon fuels up to certain limits due to its corrosivity and hydrophilicity, butanol is lipophilic and non-corrosive (New Zealand Ministry of Transport and SGS Industrial, Penrose 2009). Furthermore, it has a slightly higher energy density (36.0 MJ/L) than gasoline (34.2 MJ/L), and similar burn rate and octane number, allowing completely unmodified vehicles to run on both butanol alone and butanol/petrol fuel blends (Szulczyk, 2010;Xu and Avedisian, 2015). Butanol further allows higher ethanol concentrations to be used within blended fuels, as it solubilizes ethanol in the bulk petrol and prevents ethanol volatilization (Yanowitz et al, 2011).…”
Section: The Cost Of Carbon Capturementioning
confidence: 99%
“…6 1-Butanol is considered to be an excellent alternative to ethanol because it possesses an energy density closer to gasoline, low solubility in water and lesscorrosive nature. 7,8 1-Butanol is also a bulk platform chemical for synthesis of 1-butyl esters plasticizer, general extraction agent of perfumes and drugs, and paint solvent. 9 Although fermentation of biomass to 1-butanol has been developed, economical production on an industrial scale was reported to remain a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Butanol is a potential advanced biofuel that can be blent with gasoline and diesel. 14 Because of increased substrate costs and availability of less expensive petrochemically derived butanol in the 1950s, most of the acetone/butanol/ethanol (ABE) fermentation plants were closed. 4,5 However, in the past decade, the interest in butanol fermentation has been revived, which led multiple studies on strain development, fermentation improvement, and in situ product removal technologies.…”
Section: Introductionmentioning
confidence: 99%